Fermented soybean meal in broiler diets exposed to stress induced by corticosterone: Effect on growth performance, gut health and immune response - ABEDDARGAHI, Fakhreddin; DARMANI-KUHI, Hassan; ROOSTAIE-ALIMEHR, Mohammad; HOSSEINI-MOGHADDAM, Seyed H.; HASSAN-SAJEDI, Reza; HOSSEINI, Anahid; MOHAMMADPOUR, Fatemeh (Spanish Journal of Agricultural Research, 2023)
Aim of study: To investigate the effect of fermented soybean meal (FSBM) on responses of broiler chickens exposed to stress condition.Material and methods: Two hundred and eighty-eight day-old male chickens were allocated to six treatments in a 2 × 3 completely randomized factorial design involving two factors: factor 1 was the subcutaneous injections of CORT or corn oil (as control) at 2 mg/kg body weight twice per day during 3 days; and factor 2 were 3 levels (0, 10 and 20%) of FSBM in replacement of the original soybean meal.Main results: The replacement of soybean meal by FSBM increased FI and BWG without any significant effect on FCR (10 days), while FCR was increased significantly by CORT injection. Corticosterone injection caused a significant decrease in the ratio of villus height (VH) to crypt depth (CD) in the duodenum and jejunum. The height of villi in the duodenum increased significantly at 20% FSBM replacement. The antibody titers against Newcastle disease (28 and 2 day), coliform count (28 day) and activity of digestive enzymes (10 day) were not affected by either FSBM replacement or CORT injections. Corticosterone injection significantly increased tall-like receptor-4 (TLR4) and immunoglobulin A (IgA) expression, while decreased heat shock protein-70 (HSP70) expression. FSBM replacement down-regulated the expression of TLR4, HSP70, and IgA in small intestine compared to the control group. In stress condition induced by CORT injection, 10% FSBM replacement decreased HSP70 and IgA expression in the jejunum and ileum, while had no effects on TLR4.Research highlights: Partial replacement of soybean meal by FSBM in diets had positive effects on performance, intestinal morphology and immune response in chicks exposed to stress.